Assessment of the long-term outcomes following potentially traumatic events – the CONNECT study - Priebe, S. (Array, 2005)
There has been little systematic research on long-term clinical and social outcome of people who experienced potentially traumatic events in armed conflict. In particular, it is unclear how refugees differ from people who stayed in the area of conflict, and what the relative impact of social and specific health care intervention on long-term outcome is. The CONNECT addresses the related research questions. Description of the rationale, approach and methodology of the study. Results. CONNECT is a collaborative study funded by the Research Directorate of the European Commision with centres in Bosnia-Herzegovina, Croatia, Germany, Italy, Mazedonia, Serbia and the United Kingdom. In each country people who experienced potentially traumatic events due to war and forced migration during the Balkan conflict will be screened and interviewed. The intended total sample will be more than 4000 people. History of potentially traumatic experiences, received social and health care interventions, current psychopathology and quality of life will be assessed. A subgroup of 800 people will be identified who suffer from ongoing symptoms of post-traumatic stress and followed up over one year period. CONNECT is the largest project of its kind that has been initiated in Europe. It is unusual in several respects and carries significant risks. The study aims to deliver important results and strengthen the collaborative academic links between the participating countries.